Some autecological data on the Urodeles of Sardinia - Voesenek, L.A.C.J.; van Rooy, P.T.J.C.; Strijbosch, H (Amphibia-Reptilia, 1987)
In the spring of 1984 an ecological investigation on the endemic salamanders Hydromantes genei flavus and Euproctus platycefihalus was carried out in eastern Sardinia. The investigation was focussed on natural population sizes and densities. The Sardinian cave salamander was found to occur in two clearly distinct habitats, viz. humid holm oak forests and limestone caves. The density found in the forests was 300/ha and 98 ± 7 individuals were found in one cave. The Sardinian brook salamander was found in a habitat not reported before, viz. a stagnant mountain lake. There the animals were rather robust, and a neotenic specimen was captured.
Keywords: Euproctus platycefihalus; Hydromantes genei flavus; Sardinia (PG)